The Spirituality of Modern Society: Between Escapism and The Illuminati - Fathin Fauhatun; Nunu Burhanuddin (University of Darussalam Gontor, Indonesia, 2022)
This article describes the visible conditions of modern human development that display a different phenomenon. Previously, they were famous for their all-materialistic lifestyle, but now they seem to be heading towards spiritual things. On the one hand, this shows a good change. If you pay close attention to this phenomenon, you can see that there is a tug of war between escapism and illuminates, whether the shift of modern human attention to the spiritual is only limited to escapism to avoid the hustle and bustle they experience or illuminates who make themselves aware of the importance of a balance between physical and spiritual needs. This research uses the library research method using deductive-inductive logic reflectively. Discussing this matter, Sufism as the direction that modern humans go in meeting spiritual needs can help humans not only focus on human problems with God but also on issues related to humans and their social realm, Sufism can be relevant to modern life. Thus the balance between the outer and inner aspects can be realized and the shift of humans to the Sufism aspect is an escape (escapism) that leads to enlightenment (illuminati).